Photoelectrochemical cell for P–H/C–H cross-coupling with hydrogen evolution. Issue 70 (6th August 2019) - Wang, Jing-Hao; Li, Xu-Bing; Li, Jian; Lei, Tao; Wu, Hao-Lin; Nan, Xiao-Lei; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : A photoelectrochemical cell is able to save nearly 90% external bias input to realize activation of P–H/C–H bonds for cross-coupling hydrogen evolution as compared with an electrochemical cell. Abstract : Photoelectrochemistry enables the formation of a variety of active intermediates for organic synthesis in an environmentally friendly manner. Herein, a photoelectrochemical cell is fabricated to realize activation of P–H/C–H bonds for cross-coupling hydrogen evolution. As compared with an electrochemical cell, nearly 90% external bias input is saved to drive the C–P bond construction with good to excellent yields.